Hemolytic uremic syndrome associated with Escherichia coli O157:H7 infection in older adults: a case report and review of the literature. (December 2016) - Ko, Heidi; Maymani, Hossein; Rojas-Hernandez, Cristhiam
Abstract Background Hemolytic uremic syndrome associated with Shiga toxin-producingEscherichia coli O157:H7 has been widely known as a common cause of acute renal failure in children. There are only a few reports of sporadic Shiga toxin-producingEscherichia coli -hemolytic uremic syndrome in adults in the USA. Analyses from the 2011 outbreak of hemolytic uremic syndrome associated withEscherichia coli O104:H4 reported that mortality rates are highest in those patients with age >60-years old. Therefore, recognizing Shiga toxin-producingEscherichia coli -hemolytic uremic syndrome in older people can help early introduction of the appropriate therapy. Case presentation We describe an 86-year-old Caucasian woman, initially treated as suspected thrombotic thrombocytopenic purpura, with worsening neurological and renal functions despite plasmapheresis (plasma exchange). A subsequent normal ADAMTS13 activity level and positive stool sample forEscherichia coli O157:H7 confirmed the diagnosis of Shiga toxin-associated hemolytic uremic syndrome. We shifted our management towards aggressive supportive care. Despite conventional treatment, hemolytic uremic syndrome unfortunately led to her death. Conclusions Our case demonstrates the importance of recognizing Shiga toxin-producingEscherichia coli -hemolytic uremic syndrome as an etiology of microangiopathic hemolytic anemia in older people. According to the current literature, supportive care is the best approach for Shiga toxin-producingEscherichia coli -hemolytic uremic syndrome. Therapies such as plasma exchange and eculizumab (a complement inhibitor) are not shown to be effective in Shiga toxin-producingEscherichia coli -hemolytic uremic syndrome. There is a dire need to continue research to find better treatment options in this disease entity with a high mortality, particularly in older people.